Evaluation and awareness of over the counter use of non-steroidal anti-inflammatory drugs - Parinaz Amirimoghadam, Bahare Zihayat, Fatemeh Dabaghzadeh, Kioomars Kiani, Javad Ebrahimi, Mehran Ghazanfari, Shokouh Arjmand (Journal of Applied Pharmaceutical Science, 2017)
Objectives: Non-steroidal anti-inflammatory drugs are among the drugs with the highest prevalence of use (with or without prescription). While a notable percent of patients have incomplete knowledge about appropriate use of over the counter drugs. The aim of the current study was to evaluate the pattern of over the counter use of non-steroidal anti-inflammatory drugs and also the public knowledge about different aspects of over the counter use of non-steroidal anti-inflammatory drugs such as adverse effects, proper dose and drug interactions with concurrent medications.Material and methods: The in-charge pharmacists of the 10 pharmacies asked purchaser the important questions about OTC use of NSAIDs and then recorded the responses using face-to-face interviewing. The in-charge pharmacists interviewed with 600 NSAIDs purchasers during the study.Results: More than half of all the purchasers received non-steroidal anti-inflammatory drugs use recommendation either by physicians or pharmacists. But less than 35% of the purchasers had been informed by the physicians or pharmacists about drug interactions, adverse effects and proper use of non-steroidal anti-inflammatory drugs. It was found 63.8% of the customers used non-steroidal anti-inflammatory drugs as needed and 23.3% of them used usual dose. In addition, 92.5% and 79.2% of the consumers were not aware of non-steroidal anti-inflammatory drugs drug interactions and side effects, respectively. The most prevalent concurrent medical conditions were cardiovascular diseases (12.2%).Conclusion: The level of public knowledge regarding non-steroidal anti-inflammatory drugs was low.
Keywords: Knowledge, non-steroidal anti-inflammatory drugs, over the counter drugs, pharmacists.